Justifying health IT investments: A process model of framing practices and reputational value. Issue 4 (December 2018) - Polykarpou, Stavros; Barrett, Michael; Oborn, Eivor; Salge, Torsten Oliver; Antons, David; Kohli, Rajiv
Abstract: Despite important research contributions on the financial and operational dimensions of information technology (IT) value, justifying health IT (HIT) investments remains a difficult and enduring issue for IT managers. Recent work has expanded our understanding of HIT value, by focusing on the initial resource allocation stage, and through conceptualizations of value across multiple dimensions. Building on these developments, we adopt a performative perspective to examine the research question of how practitioners justify early stage HIT investments, with a focus on reputational value. We explored this question through a comparative field study of two hospital organizations in the English National Health Service (NHS). We found that practitioners' temporally orientated framing practices matter in justifying HIT investments, enacting different possibilities for reputational value. We develop a process model to explain these dynamics and highlight the mutability of reputational value, which can lead to different possibilities for restoring, enhancing, or maintaining reputation. We conclude by discussing the implications for justifying HIT investments. Highlights: We study how practitioners at two hospital organizations facing different reputational circumstances justified IT investments. We develop a performative framing framework to unpack how temporal practices enact reputational value possibilities. We demonstrate how reputational value is performed differently, through the ongoing process of justifying HIT investments. We contribute a process model of framing practices and reputational value oriented towards the past, present and future.